Equality higher education for the XXI century. - Vega Miranda, Alexander (2011)
This article aims to present the explicitly the series of ideological and pedagogicalgicas that within the Costa Rican context, must be taken into account by the person collecting thedecisions, when trying to improve the quality of education to meet the challenges of the XXI century.